If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + -89 = 100 + 5x Reorder the terms: -89 + -2x = 100 + 5x Solving -89 + -2x = 100 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -89 + -2x + -5x = 100 + 5x + -5x Combine like terms: -2x + -5x = -7x -89 + -7x = 100 + 5x + -5x Combine like terms: 5x + -5x = 0 -89 + -7x = 100 + 0 -89 + -7x = 100 Add '89' to each side of the equation. -89 + 89 + -7x = 100 + 89 Combine like terms: -89 + 89 = 0 0 + -7x = 100 + 89 -7x = 100 + 89 Combine like terms: 100 + 89 = 189 -7x = 189 Divide each side by '-7'. x = -27 Simplifying x = -27
| 3t/4=6 | | 34/3.14= | | -12/5=p | | 2(x+4)-3=7+3x-2 | | -23+10x=8x+17 | | 3xy+4-xy-xy+10+y+5x= | | -7m+13=14m | | 3x-87=33-5x | | 2x=6-8x | | (u+3)*7=16 | | -6=d/18 | | C=(3.14)r | | (x^2)+3z=0 | | 24+m=-93 | | -10x-143=7x+78 | | 32=18 | | x+2=-4-2x | | (x+4)(2x+2)= | | x^2-2x+400=0 | | 25=5+.50x | | (q-3)*2=16 | | 12x-31=38+9x | | 5x+3=-x+21 | | 2x(4x-7)= | | 8+p=9 | | -x-17=11-2x | | 3-v+3=1-4v+1 | | -66+x=9x+62 | | 16x+21=46-y | | -7=-7x-3(-x+17) | | G=7F+6 | | -34-8x=29-11x |